Prospects for the use of ash and rock waste as a secondary resource in the energy industry (Международный научный журнал «Инженер», 2026)
This article analyzes the environmental and economic problems of fly ash and aggregates, which arewaste coal fuel at thermal power plants (TPP), as well as the possibilities of their effective use in theproduction of building materials. The article analyzes the use of fly ash in concrete and cement, methodsfor improving its physical, chemical and mechanical properties, based on scientific research and foreignpatents. In order to save resources in construction and protect the environment, special attention is paidto the technologies for processing TPP waste and their efficiency. At the same time, based on the appliedmethodology, geological surveys and experimental tests, methods for preparing concrete and blocksbased on fly ash are recommended